Short-term blood pressure variability outweighs average 24-h blood pressure in the prediction of cardiovascular events in hypertension of the young. Issue 7 (July 2019) - Palatini, Paolo; Saladini, Francesca; Mos, Lucio; Fania, Claudio; Mazzer, Adriano; Cozzio, Susanna; Zanata, Giuseppe; Garavelli, Guido; Biasion, Tiziano; Spinella, Paolo; Vriz, Olga; Casiglia, Edoardo; et al.
Abstract : Objective: The association of short-term blood pressure (BP) variability (BPV) with cardiovascular events (CVEs) is controversial. Aim of this study was to investigate whether BPV measured as weighted 24-h SD was associated with CVE in a prospective cohort study of young patients screened for stage 1 hypertension. Methods: We performed 24-h ambulatory BP monitoring in 1206 participants aged 33.1 ± 8.5 years, untreated at baseline examination. Participants were divided into two categories with low (<12.8 mmHg) or high (≥12.8 mmHg) SBPV. Hazard ratios for CVE associated with BPV expressed either as continuous or categorical variable were computed from multivariable Cox models. Results: During 15.4 ± 7.4 years of follow-up there were 69 fatal and nonfatal CVE. In multivariable Cox models, high SBPV was an independent predictors of CVE [2.75 (1.65–4.58); P  = 0.0001] and of coronary events [3.84 (2.01–7.35), P  < 0.0001]. Inclusion in the model of development of hypertension requiring treatment during the follow-up, did not reduce the strength of the associations. Addition of SBPV to fully adjusted models had significant impact on risk reclassification and integrated discrimination (relative integrated discrimination improvement for BPV as continuous variable: 13.5%, P  = 0.045, and for BPV as categorical variable: 26.6%, P  = 0.001). When the coefficient of variation was used as BPV metric similar results were obtained. Of note, in all Cox models average 24-h BP was no longer an independent predictor of outcome after BPV was included. Conclusion: Short-term BPV adds to the risk stratification for cardiovascular events in young-to-middle-age patients screened for stage 1 hypertension over and above traditional 24-h ambulatory monitoring indexes. Abstract : Supplemental Digital Content is available in the text